MODULATION OF UCP2 EXPRESSION BY P38 - A LINK TO CARDIOPROTECTION - Valouskova, Eva; Modriansky, Martin (Biomedical papers, 2008)
Background: Discovery of uncoupling protein 2 (UCP2) in 1997 and demonstration of its wide tissue expression has triggered an important question about controlled oxidative phosphorylation uncoupling and the physiological function of this process. Uncoupling protein 2 (UcP2) is a mitochondrial protein that can influence the mitochondrial membrane potential and hence the production of reactive oxygen species by mitochondria. It is also thought to be involved in apoptotic signaling pathways and it has been suggested to be important in cardio- and neuroprotection.Methods and results: We examined the recent literature (2003-2007) in the MedLine database for evidence linking p38, one of the stress-related protein kinases, with modulation of UCP2 expression in the heart. While two reports clearly demonstrate p38 as down-regulating UcP2 expression, only circumstantial evidence exists for cardiomyocytes. Conflicting results on p38-regulated cardiomyocyte survival after ischemia leave an open venue for hypotheses on the differential regulation of protein expression, including UCP2.Conclusions: Reviewing the evidence connecting UCP2 and its cytoprotective activities, we propose a tissue specific link that may explain the variable influence of p38 via modulation of UCP2 expression.
Keywords: Mitochondria/Oxidative phosphorylation/Uncoupling/Mitogen-activated protein kinase/Reactive oxygen species